N‐Terminal Pro–Brain Natriuretic Peptide (NT‐proBNP) Levels are Increased in Patients With Transient Ischemic Attack Accompanied by Nonfocal Symptoms. Issue 12 (December 2015) - Plas, Gerben J. J.; Jurg, Susanne D.; Brusse‐Keizer, Marjolein; Dippel, Diederik W. J.; Koudstaal, Peter J.; den Hertog, Heleen M.
Abstract : Background: Transient nonfocal neurological symptoms may serve as markers of cardiac dysfunction. We assessed whether serum N‐terminal pro–brain natriuretic peptide (NT‐proBNP) levels, a biomarker of cardiac disease, are increased in patients with transient ischemic attack (TIA) accompanied by nonfocal symptoms and in patients with attacks of nonfocal symptoms (transient neurological attack [TNA]). Methods and Results: We included 15 patients with TNA, 69 with TIA accompanied by nonfocal symptoms, 58 with large‐vessel TIA, 32 with cardioembolic TIA, and 46 age‐ and sex‐matched healthy control participants. Serum NT‐proBNP levels were determined within 1 week after the attack. We compared log‐transformed NT‐proBNP levels of patients with cardioembolic TIAs and mixed or nonfocal TNAs, with those of patients with noncardioembolic TIAs as a reference group. Adjustments for age, sex, atrial fibrillation, and a history of nonischemic heart disease were made with a multiple linear regression model. Compared with large‐vessel TIA (mean 14.2 pmol/L), mean NT‐proBNP levels were significantly higher in patients with TIA accompanied by nonfocal symptoms (40.5 pmol/L, P =0.049) and with cardioembolic TIA (123.5 pmol/L; P =0.004) after adjustments for age, sex, atrial fibrillation, and a history of nonischemic heart disease. Patients with TNA also had higher mean NT‐proBNP levels (20.8 pmol/L, P =0.38) than those with large‐vessel TIA, but this difference was not statistically significant. Conclusion: NT‐proBNP levels are increased in patients with TIA accompanied by nonfocal symptoms.